Osteogenesis at implants without primary bone contact - An experimental study in dogs - Sivolella, Stefano; Bressan, Eriberto; Salata, Luiz A.; Urrutia, Zoraya A.; Lang, Niklaus P.; Botticelli, Daniele (Wiley-Blackwell, 2012)
Aim: To evaluate the healing at implants with a moderately rough surface placed and stabilized in recipient sites of dimensions deeper and larger than that of the implants to avoid any contact between parent bone and the implant.Material & methods: In six Labrador dogs, premolars and first molars were extracted bilaterally in the mandible. After 3 months of healing, mucoperiosteal full-thickness flaps were elevated and the premolar area of the alveolar bony crest was selected. Three recipient sites were prepared to place three implants. One implant was used as control. The other two were placed in recipient sites which left a circumferentially and periapical prepared defect of 0.7 mm (small) and 1.2 mm (large), respectively. All implants were stabilized with passive fixation plates to maintain the implants stable and without any contact with the implant bed. After 3 months of submerged healing, the animals were sacrificed. Ground sections were prepared and analyzed histomorphometrically.Results: The BIC% was 5.3% and 0.3% for implants placed in small and large defect sites, respectively, whereas it was 46.1% for control implants. The differences were statistically significant. The width of the residual defects was 0.4 and 0.5 mm at the small and large defects, respectively. An approximately 0.09 mm layer of dense connective tissue (DCT) rich in fibers and fibroblast-like cells was observed adherent to the implant surfaces. The percentage of implant surface covered by DCT was 92.8% and 95.6% at the small and large defects, respectively.Conclusion: Osseointegration was observed at the test sites, and the dimensions of the defects influenced the outcomes. However, the degree of osseointegration at both small and large defects was very low compared with the control sites.
Keywords: animal study; bone contact; bone healing; contact osteogenesis; defect; distance osteogenesis; implant dentistry; osseointegration